TH2.3: Strengthening climate resilience of women farmers through innovative extension approaches: Evidence from video-based extension in Kenya - Kato, Edward (International Food Policy Research Institute, 2022)
There is growing evidence that lack of equal access to information on climate resilience strategies has contributed to sub-optimal adoption of climate-resilient agricultural practices, institutions and technologies. This study rolled out innovative videos of women-identified practices to women farmers through grassroots women's groups (India and Kenya) and through the national extension service (Uganda) to more than 35,000 farmers in Gujarat, India, Kenya and Uganda. Practices identified by women farmers through qualitative fieldwork included climate smart pig and poultry management, integrated pest management, water harvesting, zai pits and conservation agriculture. The presentation will report on changes in awareness, knowledge, adoption as well as in women's empowerment in response to the intervention in Kenya and Uganda were the endline surveys were completed in early 2022. The findings are relevant to next users of video-based extension approaches, such as NGOs, the government and the private sector that are interested in reaching, benefiting and empowerment women farmers.